Income Inequality, Mobility, and Turnover at the Top in the US, 1987–2010 - Auten, Gerald; Gee, Geoffrey; Turner, Nicholas (American Economic Review, 2013)
While cross-sectional data show increasing income inequality in the United States, it is also important to examine how incomes change over time. Using income tax data, this paper provides new evidence on long-term and intergenerational mobility, and persistence at the top of the income distribution. Half of those aged 35-40 in the top or bottom quintile in 1987 remain there in 2007; the others have moved up or down. While 30 percent of dependents aged 15-18 from bottom quintile households are themselves in the bottom quintile after 20 years, most have moved up. Persistence is lower in the highest income groups.